Analysis Song Lyrics Of Towi-Towi As Social Criticism In Nias Society - Happy Majesty Waruwu; Kartini R.M. Manalu; Emmi Simangunsong (Universitas Negeri Semarang, 2025)
This study explores the meaning of the song Towi-Towi, composed by Piet Harefa, as a form of social criticism against the customary marriage law (fondrakö) of the Nias people. Written in the 1960s and later popularized by Ayu Zega in 2014, the song reflects the social struggles of Nias women who face difficulties in marriage due to the high böwö (bridewealth) determined by bosi (social status) within the traditional system. The research adopts a qualitative descriptive method supported by discographic study, literature review, and observation. Schleiermacher’s hermeneutic theory serves as the analytical framework to interpret the composer’s intention and to uncover the symbolic meanings embedded in the lyrics. The use of personification through the towi-towi bird, a local symbol of good news, becomes a poetic device through which Piet Harefa expresses the anxiety, hope, and criticism toward rigid customary norms. The findings reveal that Towi-Towi functions not merely as entertainment but as a medium of reflection and social protest that exposes gender inequality, materialism, and the moral burden imposed by the fondrakö system. The song also portrays the paradox between cultural pride and socio-economic suffering, especially among men who must comply with the demanding expectations of the traditional marriage structure. As a cultural text, Towi-Towi represents a form of musical resistance that questions the moral and ethical relevance of traditional values in a changing modern context. Thus, the song embodies both aesthetic and socio-political significance in the collective consciousness of Nias society.